Efficacy and Cost-Effectiveness of HPV-DNA Self-Sampling with Telemedicine-Supported Triage for Cervical Cancer Screening in Underserved Indonesian Populations: A Pragmatic Randomized Controlled Trial - Rachmat Hidayat; Lisye Tiur Simanjuntak; Sarah Fernandez (Sriwijaya Journal of Obstetrics and Gynecology, 2025)
Introduction: Cervical cancer screening coverage in Indonesia remains far below the WHO elimination target, because distance, lost wages, scarce female providers, and fragmented referral cause low participation and high triage attrition. We evaluated whether HPV-DNA self-sampling integrated with physician-led telemedicine triage improves screening completion and follow-up adherence and is cost-effective versus standard clinic-based screening. Methods: In a pragmatic, open-label, two-arm randomized controlled trial across two contrasting Indonesian regions—a dense metropolitan periphery (Region A) and a riverine/remote periphery (Region B)—1,032 under-screened women aged 30–50 years were randomized 1:1 to community-delivered HPV-DNA self-sampling with telemedicine triage of high-risk HPV (hrHPV)-positive results, or to standard referral for visual inspection with acetic acid or cytology. Primary outcomes were screening uptake within three months and the incremental cost-effectiveness ratio (ICER) per additional hrHPV case successfully triaged. Analysis followed intention-to-treat with multivariable logistic regression. Results: Screening uptake was 82.0% versus 48.1% (risk ratio 1.71, 95% CI 1.55–1.88; absolute difference 33.9%, number-needed-to-invite 3; adjusted odds ratio 4.94, 95% CI 3.72–6.56, p<0.001), consistent across regions (interaction p=0.42). Among hrHPV-positive women, follow-up adherence was 92.7% (38/41) versus 57.1% (12/21) (odds ratio 9.50, 95% CI 2.28–39.6, p=0.003), and CIN2+ was detected and treated in 11 versus 3 women. Cost per successful follow-up was US$315 versus US$516; the intervention was dominant in 96% of probabilistic simulations. Conclusion: Integrating HPV self-sampling with physician-led telemedicine triage substantially increased both screening and triage completion across diverse geographies while remaining cost-effective. National programs should embed telemedicine-supported triage to close the cervical-screening cascade.